2019
DOI: 10.1021/acs.joc.9b00642
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Intramolecular Silylperoxidation of Unsaturated Diisopropylsilyl Ethers

Abstract: A cobalt-catalyzed intramolecular silylperoxidation reaction was developed that allows for the conversion of unsaturated diisopropylsilyl ethers to 3-sila-1,2,4-trioxepanes. Reduction of the peroxide unit of the 3-sila-1,2,4-trioxepane yields six-membered ring diisopropylsilylene acetals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…18,19 There is one example from the Lee laboratory of the use of silanols for gold-catalyzed alkyne functionalization 20 and an example of a silylperoxidation reaction of homoallylic alcohols from the Woerpel laboratory. 21 Nevertheless, our survey of the literature revealed no examples of the silanol tether employed in alkene functionalization. Our work has been directly inspired by the pioneering contributions of Overman 22,23 and Leighton, 24−28 who demonstrated that acetal tethers could be used for the mercuric salt-mediated functionalization of olefins (Scheme 1).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…18,19 There is one example from the Lee laboratory of the use of silanols for gold-catalyzed alkyne functionalization 20 and an example of a silylperoxidation reaction of homoallylic alcohols from the Woerpel laboratory. 21 Nevertheless, our survey of the literature revealed no examples of the silanol tether employed in alkene functionalization. Our work has been directly inspired by the pioneering contributions of Overman 22,23 and Leighton, 24−28 who demonstrated that acetal tethers could be used for the mercuric salt-mediated functionalization of olefins (Scheme 1).…”
mentioning
confidence: 95%
“…The resulting cyclic silanediol compounds, reminiscent of intermediates en route to polyol natural products (Figure ), are synthons for a variety of further transformations. Silanol auxiliaries have been popularized by Gevorgyan and co-workers as directing groups in C–H functionalization reactions. , There is one example from the Lee laboratory of the use of silanols for gold-catalyzed alkyne functionalization and an example of a silylperoxidation reaction of homoallylic alcohols from the Woerpel laboratory . Nevertheless, our survey of the literature revealed no examples of the silanol tether employed in alkene functionalization.…”
mentioning
confidence: 99%
“…Tethered alkene functionalization reactions allow the synthetic chemist to transform olefins with unusual precision. Because of the predisposition for six- and seven-membered cyclic transition states, one can simply count the number of atoms from the nucleophilic auxiliary (“the tether”) where the functionalization event is likely to take place; due to geometric constraints, these reactions generally proceed with high regio- and diastereoselectivity. Our laboratory is deeply invested in developing tethered olefin functionalization reactions, and we have disclosed such reactions using sulfamate, , phosphoramidate, and di- tert -butylsilanoxy tethers. , …”
mentioning
confidence: 99%
“…Tethered alkene functionalization reactions allow the synthetic chemist to transform olefins with unusual precision. [1][2][3][4][5][6][7] Because of the predisposition for six-and sevenmembered cyclic transition states, one can simply count the number of atoms from the nucleophilic auxiliary ("the tether") where the functionalization event is likely to take place; due to geometric constraints, these reactions generally proceed with high regio-and diastereoselectivity. Our laboratory is deeply invested in developing tethered olefin functionalization reactions, and we have disclosed such reactions using sulfamate, 8,9 phosphoramidate, 10 and di-tert-butyl-silanoxy tethers.…”
mentioning
confidence: 99%